Achieving Blessings Through the Flagship Zero Waste Program at SMAN 4 Mataram - Jauhari Khalid; Ni Komang Purnawati (Wise Education, 2024)
Waste creates cultural problems as it impacts various aspects of life sustainability. Consequently, humans are dependent on their surrounding environment, making it crucial to preserve it to prevent existing issues from escalating into more significant hazards. One of the efforts that can be initiated early on from the school level to address environmental issues is the implementation of zero waste practices. The zero waste program at SMAN 4 Mataram has significantly improved the school environment and the surrounding community. This program, which includes initiatives such as saberling, waste tickets, maggot cultivation, compost production, and classroom cleanliness competitions, has effectively reduced waste volume and created a cleaner, healthier environment. Increased awareness and participation in waste management practices among students and staff have been notable outcomes, alongside the development of waste-based entrepreneurship. Data collection methods include observation, interviews, and surveys to assess the program's effectiveness and impact. he zero waste program at SMAN 4 Mataram has improved the community's well-being by creating a healthier environment and reducing health risks associated with waste accumulation. The program has instilled a sustainable environmental culture among students and staff, which can be passed on to future generations. For similar practices, it is recommended to enhance infrastructure and continually engage the community in environmental education and activities.